ANALYSIS OF ILLOCUTIONARY SPEECH ACTS IN THE LYRICS OF THE SONG GARAM DAN MADU: A PRAGMATIC AND SEMIOTIC STUDY OF REPRESENTATIVE, DIRECTIVE, COMMISSIVE, AND EXPRESSIVE ACTS - Ira Kusmira (PT. Media Akademik Publisher, 2026)
This study aims to analyze the types and functions of illocutionary speech acts found in the lyrics of the song “Garam dan Madu” performed by Tenxi, Naykilla, and Jemsii. The song was selected due to its rich linguistic expressions and its potential to convey complex pragmatic and semiotic meanings. This research employs a descriptive qualitative method combined with a pragmatic and semiotic approach. Data were collected through observation, documentation, and note-taking techniques, with the song lyrics serving as the primary data source. The units of analysis consist of utterances that contain illocutionary acts, which are then categorized into representative, directive, commissive, and expressive types. The findings reveal a total of 17 data points, consisting of six representative acts, three directive acts, three commissive acts, and five expressive acts. These results indicate that representative acts are the most dominant, reflecting the speaker’s tendency to convey personal beliefs, emotions, and experiences. Furthermore, the analysis shows that the lyrics not only function as artistic expressions but also as meaningful communicative tools that reflect emotional depth, interpersonal relationships, and social context. By integrating pragmatic and semiotic perspectives, this study contributes to a deeper understanding of how language in song lyrics operates beyond aesthetic value, serving as a medium for expressing complex meanings and human experiences.